Physical Activity Engagement Across Human Life Cycles: A Scoping Review - Castro, Rafael Luis G.; Manalansan, Lenard M.; Sibug, Vanessa B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Physical activities bring health benefits essential to an individual's overall well-being. Engagement in physical activities may vary across different ages, gender, and the capability of an individual to participate. Despite the many potential benefits, the uptake of the level of physical activities among individuals is quite low and risk may occur that depends on the environment they are in. To elucidate these benefits and factors of physical activity engagement of individuals, this study aimed to classify all the scope of the evidence that pertains to participation in physical activities. The literature research, conducted in 2022, employed the databases Education Resources Information Center (ERIC), PubMed, ScienceDirect, and the search engine Google Scholar. Twenty-nine studies mentioning the engagement of individuals in physical activities were tagged from 4 databases. Findings equivalent to the article and participants were summarized quantifiably, while information implying the engagement in physical activities was organized using thematic analysis. Results distinguished that level of engagement in physical activities may vary in age, gender, and capabilities. These also identified risks that may occur in too much participation in activities or not even participating. Most importantly, physical activities were beneficial to an individual's physiological, personal, and psychosocial aspects. Understanding the engagement and establishment of community-based activities with the characteristics of inclusivity that will increase the level of engagement and participation of every individual may be functional to increase the promotion of physical activities regardless of their age, gender, and capabilities to perform.